Computer‐Aided High Tibial Osteotomy—A Comparative Study of Commonly Used 3D Printing Technology and Navigation Application - Elvis Chun‐Sing Chui; Kyle Ka‐Kwan Mak; Randy Hin‐Ting Ng; Ericsson Chun‐Hai Fung; Mei‐Shuen Chan; Kai Yue; Lawrence Chun‐Man Lau; Clifford Long‐Fung Chan; Edmond Wing‐Fung Yau; Wei Zhao; Xiuyun Su; Jin Zhang; et al. (Orthopaedic Surgery)
ABSTRACT Background High tibial osteotomy (HTO) is a surgical procedure for treating certain knee conditions. Proper execution of HTO can preserve joint function and delay or avoid the need for total knee replacement. This study compared different 3D printing techniques (fused deposition modeling, selective laser sintering, and direct metal laser sintering) and a navigation system for their suitability in assisting HTO surgeries. Methods Tibial saw‐bones were used as models, and surgical guides and the navigation system were employed during the procedures. Six parameters (planning time, manufacturing time, delivery time, material cost, operation time, and accuracy) were evaluated. One‐way analysis of variance (ANOVA) and t‐test were used for the analysis. Results The results showed that the metal surgical guides had the highest accuracy (angle differences mean, 2.4°) and operation time (mean 9.75 min), followed by plastic guides, classic guides, and the navigation system. The differences in accuracy were attributed to factors like rigidity, melting point, and errors during incisions. Conclusions The study recommended metal surgical guides as the best option for assisting HTO due to their accuracy and operation time. And the results have implications for orthopedic surgeons performing HTO surgeries, as they can use this information to improve postoperative outcomes, such as mechanical axis alignment and quality of life for HTO patients.